Ambiguity aversion solves the conflict between efficiency and incentive compatibility - Luciano I. De Castro; Nicholas C. Yannelis (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2010)
The conflict between Pareto optimality and incentive compatibility, that is, the fact that some Pareto optimal (efficient) allocations are not incentive compatible is a fundamental fact in information economics, mechanism design and general equilibrium with asymmetric information. This important result was obtained assuming that the individuals are expected utility maximizers. Although this assumption is central to Harsanyi's approach to games with incomplete information, it is not the only one reasonable. In fact, a huge literature criticizes EU's shortcomings and propose alternative preferences. Thus, a natural question arises: does the mentioned conflict extend to other preferences? We show that when individuals have (a special form of) maximin expected utility (MEU) preferences, then any efficient allocation is incentive compatible. Conversely, only MEU preferences have this property. We also provide applications of our results to mechanism design and show that Myerson-Satterthwaite's negative result ceases to hold in our MEU framework.
Keywords: D50; D81; D82; 330; asymmetric information; ambiguity aversion; incentive compatibility; mechanism design; first-best; second-best